A copper-catalyzed sulfonylative C–H bond functionalization from sulfur dioxide and aryldiazonium tetrafluoroborates. Issue 3 (18th October 2017) - Xia, Hongguang; An, Yuanyuan; Zeng, Xincheng; Wu, Jie
Abstract : Sulfonylative C–H bond functionalization through a copper-catalyzed three-component reaction of 8-aminoquinoline amides, DABCO·(SO2 )2 and aryldiazonium tetrafluoroborates is developed. Excellent selectivity in the para -position is observed. Abstract : Sulfonylative C–H bond functionalization through a copper-catalyzed three-component reaction of 8-aminoquinoline amides, DABCO·(SO2 )2 and aryldiazonium tetrafluoroborates is developed. Excellent selectivity in the para -position is observed for this copper-catalyzed transformation. This reaction is triggered by a copper-chelated complex via the coordination of the copper catalyst with the substrate and arylsulfonyl radical generated in situ, thus providing 5-sulfonyl-8-aminoquinoline amides in moderate to good yields.